Tribal Sub Plan of Kerala 1980-85 and 1981-82 (Draft) - Planning Commission (Planning Commission, 1980)
The Sub Plan strategy of area development approach with focus on Tribals was first adopted in the State during 1976. Following are the Integrated Tribal Development Project Areas Identified in the State :2. Prior to 1976, Attappady was a Community Tribal Development Block. In 1976, it was converted into an Integrated Tribal Development Project and a Project Report prepared. No Projects as such have come into existence in the four other Project areas but development efforts were continued there also with the existing administrative machinery.
Tribal Welfare Department Government of Kerala